Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Pegawai di Fakultas Ilmu Sosial dan Politik UNISBA Blitar - Sutowo, Sutowo; Sudiasmo, Fandi (Universitas Islam Balitar, 2022)
The success of an organization departs from the ideal performance and quality of human resources. The study aims to see whether motivation and work discipline partially and simultaneously influence the performance of employees at the Faculty of Social and Political Sciences of UNISBA Blitar. This research is classified as quantitative field with the spread of questionnaires to be analogous to existing theories. Data collection through observation, which is followed by questionnaires, and literature studies. Data processing methods with (a) validity tests, (b) reability, (c) classical assumptions (normality, multicollinerity, autocorrelation and heteroskesdasticity), (d) multiple linear regression analysis, (e) correlation coefficient test, (f) determination coefficient test and (g) F test and t test (hypothesis test). From the measurements made produce partially indicating the value of the sig. 0.019<0.05, meaning that motivation (X1) affects employee performance and sig value. From the work discipline of 0.000<0.05, it means that there is a significant influence on employee performance. Meanwhile, the two variables motivation (X1) and work discipline (X2) simultaneously influence the performance of employees at the Faculty of Social and Political Sciences of UNISBA Blitar.